Stakeholders’ practices: a challenge to earthquake risk mitigation decisions - Egbelakin, Temitope; Wilkinson, Suzanne; Potangaroa, Regan; Rotimi, James (International Journal of Strategic Property Management, 2015)
Enhancing building owners’ earthquake risk preparedness has been a major challenge in many seismically active regions. Many property owners are found unwilling to adopt adequate risk mitigation measures in their earthquake-prone buildings, despite the availability of various technical design solutions and the enactment of intervening legislative frameworks necessary to facilitate successful earthquake risk preparedness. This paper examined the rationale behind building owners’ unwillingness to adopt adequate mitigation measures with a view to improve current stakeholders’ practices in earthquake risk mitigation. Using a mixed-method approach, comprising both qualitative and quantitative methods, an examination of the decision-making process and different stakeholders involved in earthquake risk mitigation and the property market, provided insights into the causal agents and stakeholder practices that pose challenges to property owners’ mitigation decisions. Stake-holder practices acting as impediments revealed are property valuation assessment of retrofitted and non-retrofitted EPBs, lack of demand for improved performance in older buildings, high earthquake insurance policy premiums and deductibles, and lack of a risk assessment information system. An in-depth understanding of these challenges highlights the need for a holistic approach that should incorporate market-based incentives necessary for successful earthquake preparedness by building owners, and for designing effective strategies for improving earthquake risk mitigation. First Publish Online: 23 Dec 2015